Once Again Why Lexicography Is Science - Margalitadze, Tinatin (Lexikos, 2018)
The article addresses some issues connected with the disciplinary status of lexicography. Drawing on the views of scholars such as L. Zgusta, R. Ilson, H. Wiegand, R. Gouws, H. Bergenholtz, S. Tarp, R. Lew and others, the author argues in favour of the viewpoint that lexicography is a science and that working on a dictionary is a scientific activity. The main issues tackled in the paper include understanding the complex nature of word meaning, the role of dictionaries in the description of word meaning and the development of lexical semantics. Attention is also paid to the definitional method of the study of word meaning, which is based on the analysis of dictionary definitions, components of the theory of lexicography, the relation between lexicographic theory and practice, and the teaching of lexicography as an academic discipline at universities. The author argues that the right approach to lexicography and its disciplinary status is particularly important in our era of globalisation. Only state-of-the-art lexicographic and corpus resources will secure the future of many languages, particularly lesser-used languages, and such resources will not be created until lexicography receives proper recognition as a science with "big interdisciplinary vocation" (Tarp 2017); until lexicography is turned into an academic discipline through advanced theory of lexicography, through teaching lexicography at universities, etc.